The Oxford handbook of gender, war, and the Western world since 1600 - Hagemann, Karen (Oxford University Press, 2020)
To date, the history of military and war has focused predominantly on men as historical agents, disregarding gender and its complex interrelationships with war and the military. The Oxford Handbook of Gender, War, and the Western World since 1600 investigates how conceptions of gender have contributed to the shaping of war and the military and were transformed by them. Covering the major periods in warfare since the seventeenth century, the Handbook focuses on Europe and the long-term processes of colonization and empire-building in the Americas, Asia, Africa and Australia. Thirty-two essays written by leading international scholars explore the cultural representations of war and the military, war mobilization, and war experiences at home and on the battle front. Essays address the gendered aftermath and memories of war, as well as gendered war violence. Essays also examine movements to regulate and prevent warfare, the consequences of participation in the military for citizenship, and challenges to ideals of Western military masculinity posed by female, gay, and lesbian soldiers and colonial soldiers of color. The Oxford Handbook of Gender, War, and the Western World since 1600 offers an authoritative account of the intricate relationships between gender, warfare, and military culture across time and space.